“Today There Are No Happy People”: Antoni Godziemba Wysocki’s Journey to a Psychiatric Institution. Dom zdrowia as a Voice in Nineteenth-Century Representations of People with Mental Dysfunction - Ostrowski, Kamil (Representations of Disability in Cultural Spaces, 2026)
Mental dysfunctions are a topic that began to be widely discussed in medical discourse in the 19th century. access can also be seen in the genealogical origins of modern psychiatry. At the same time, with the advent of Young Poland, mental illness committed by the writer in their works. This is the case with Antoni Godziemba Wysocki, who re-reads Sztyrmer, Kraszewski, but also people from the world of science, creating his collection of sketches Dom zdrowia. In an article on the use that poses a threat to sick people in the 19th century, the use of which is incomparable in relation to the disease state. Note the individuals with dysfunctions identified in Wysocki’s work, which is different from what is available to the Lviv author in the works of Kraszewski and Sztyrmer.